Perlindungan Hukum Bagi Investor Retail Terhadap Transaksi Semu di Pasar Modal Indonesia - Argiyanto, Destu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Fake transactions are a stock trading strategy that often results in losses, particularly for individual investors who, in essence, have little power over the market as a whole. This conduct can jeopardize Indonesia's capital market activities' credibility and liquidity. One of the offenses classified as market manipulation under the Capital Market Law is the pseudo transaction. To put it simply, market manipulation is the act of someone making a false or misleading impression of a trading activity, market conditions, or the price of securities at a stock exchange, either directly or indirectly, or making an improper or misleading statement in order to influence the price of the securities in bursa. provisions regarding on market manipulation are provided in Articles 91, 92 and 93 of Law Number 8 of 1995 concerning the Capital Market.